Determinants of Socio-political Activity of Contemporary Youth - Наталия Усова (Российский психологический журнал, 2019)
Introduction. This paper presents a hierarchical model of socio-political activity of contemporary youth based on the system-diachronic approach. The author developed and tested a new diagnostic tool for measuring the degree of activity, intentionality, and destructiveness in subjects of social, public, and political life – a questionnaire on young people’s socio-political activity.